La convivencia institucional para la integración de los niños del inicial II en el Centro de Educación Básica “Benjamín Franklin” de la ciudad de Riobamba, periodo 2022. - Salazar Jiménez, Katiuska Solange (2022)
The objective of this research work is to analyze the institutional coexistence for the integration of initial II children in the "Benjamín Franklin" Basic Education center in the city of Riobamba, province of Chimborazo. It is based on antecedents of previous investigations and on a referential theoretical framework. It is supported by bibliographical research and is developed through descriptive and explanatory field research, with a non-experimental quantitative approach. Twelve substitute parents and the teacher in charge of Initial II of the Benjamín Franklin Basic Education Center were surveyed. The influence of institutional coexistence was investigated by studying the relationship between students as the object of study and parents, teachers and staff of the educational center as factors of influence. From the results obtained, it is concluded that institutional coexistence significantly influences the comprehensive development of children in initial II of the Benjamín Franklin Basic Education Center, in this particular case in a positive way and these reflect the importance of maintaining a good institutional coexistence. since it is a tool that helps the personal, comprehensive, physical, emotional and social development of the infant focused on strengthening parental skills based on values and principles, promoting optimal behavior in the interrelation, reaction, mediation and solution of situations in community with a harmonious environment in the educational field.